Ablation therapy following unsuccessful electrical cardioversion in patients with persistent atrial fibrillation - Hyo Jin Lee; Su Hyun Lee; Juwon Kim; Ju Youn Kim; Seung-Jung Park; Kyoung-Min Park; Young Keun On (Scientific Reports, 2024)
Abstract Electrical cardioversion (ECV) a widely utilized intervention for persistent atrial fibrillation (AF) aimed at restoring sinus rhythm. However, ECV can be ineffective, raising questions about subsequent treatment options. This study aimed to compare the outcomes of non-ablation therapy versus ablation therapy following unsuccessful ECV. A total of 125 consecutive patients with persistent AF who underwent unsuccessful ECV between November 2017 and August 2023 was included in this retrospective analysis. Of these, 51.2% received only medical therapy (non-ablation therapy group, n = 64), while 48.8% underwent AF ablation (ablation therapy group, n = 61). Various ablation methods were employed, including catheter and thoracoscopic ablation. Ablation therapy was associated with significantly better AF-free survival compared to non-ablation therapy [hazard ratio (HR), 0.37; 95% confidence interval (CI) 0.22–0.61; p < 0.01]. There was no difference of AF-free survival between catheter ablation and thoracoscopic ablation groups (HR 0.79, 95% CI 0.34–1.83; p = 0.58). AF duration > 5 year (HR 1.51; 95% CI 0.930–2.437; p = 0.10), BMI ≤ 25 kg/m2 (HR 1.61; 95% CI 1.004–2.581; p = 0.05) and diabetes (HR 2.38; 95% CI 0.902–6.266; p = 0.08) were considerable as predictor of AF recurrence. Ablation therapy following unsuccessful ECV was associated with maintaining sinus rhythm, regardless of the specific ablation method utilized.